2020
DOI: 10.17509/bs_jpbsp.v20i2.33056
|View full text |Cite
|
Sign up to set email alerts
|

Cerita Rakyat Sebagai Bahan Pengayaan Literasi Budaya Bagi Pemelajar Bipa Tingkat Menengah

Abstract: Penyusunan bahan pengayaan cerita rakyat berguna untuk meningkatkan kemampuan literasi serta membentuk pengalaman apresiasi sastra bagi pemelajar BIPA. Namun, untuk merancang bahan pengayaan yang sesuai, perlu diadakan kegiatan pendahuluan untuk menganalisis kebutuhan agar bahan pengayaan yang dirancang dapat diterima dengan baik oleh pengguna di lapangan. Penelitian ini merupakan analisis kebutuhan menggunakan metode kualitatif deskriptif. Eksplorasi kebutuhan bahan pengayaan teks cerita rakyat diperoleh mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…On the other hand, culture is the most ideal basis for studying Indonesian language including learning it for business purpose (Mussaif, 2017). It makes the involvement of culture in BIPA teaching and learning process is very important because it can reduce negative culture shock among BIPA learners (Amandangi et al, 2020). In other words, BIPA materials have to be balanced with Indonesian culture guidance to facilitate learners in actualizing and understanding Indonesian language well (Febriani et.al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, culture is the most ideal basis for studying Indonesian language including learning it for business purpose (Mussaif, 2017). It makes the involvement of culture in BIPA teaching and learning process is very important because it can reduce negative culture shock among BIPA learners (Amandangi et al, 2020). In other words, BIPA materials have to be balanced with Indonesian culture guidance to facilitate learners in actualizing and understanding Indonesian language well (Febriani et.al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…They consist of internal causes (desire and interest) and external ones (design, language, drawings, textbook design). It has also been shown that the cultural information contained in legends reveals cultural, tourist, social values and local wisdom (Amandangi et al, 2020). This information shows statistics that relate to the attitude of students towards teaching legends and legends.…”
Section: Discussionmentioning
confidence: 99%
“…Amandangi, Mulyati, and Yulianeta [20] compiled folklore enrichment materials to improve literacy skills and form literary appreciation experiences for BIPA learners. In designing appropriate materials, conducting a needs analysis activity is necessary so that the enrichment materials designed can be well received.…”
Section: Partnersmentioning
confidence: 99%